GOVERNMENT & HOUSEHOLD CONSUMPTION PATTERNS IN SURABAYA - Wijayanto, Indra (JEA17: Jurnal Ekonomi Akuntansi, 2023)
The level of household, LNPRT, and government consumption is generally seen as a measure of economic development. This reverse relationship, however, has never been studied. The purpose of this research is to analyze how the subsequent year's household and government spending will be influenced by the rate of economic growth. Using secondary data from BPS, this study quantitatively examines the municipal government of Surabaya from 2011 to 2022. The results showed that both household and government spending in Surabaya rose as the city's economy grew.